Comparative analysis of selected optimization algorithms for mobile agents’ migration pattern - Oyediran, Mayowa O.; Ajagbe, Sunday Adeola; Ojo, Olufemi S.; Elegbede, Adedayo Wasiat; Adio, Michael Olumuyiwa; Adeniyi, Abidemi Emmanuel; Adebayo, Isaiah O.; Obuzor, Princewill Chima; Adigun, Matthew Olusegun (Institute of Advanced Engineering and Science, 2024)
Mobile agents are agents that can migrate from host-to-host to work in a heterogeneous network environment. A mobile agent can migrate from host-to-host in its plan with the statistics generated on each host through a route known as migration pattern. Migration pattern therefore is the route the agents use to travel within the plan from the first host to the last host. However, there is a need for a comparison between the commonly used optimization algorithms in developing migration patterns for mobile agents with respect to some evaluation metrics. In this paper, the three techniques firefly algorithm (FFA), honeybee optimization (HBO) and particle swarm optimization (PSO) were used for developing migration patterns for mobile agents and their comparison was done based on migration time, time complexity and network load as metrics. PSO is discovered to perform better in terms of network load with an average of 242.3905 bits per second (bps), time complexity with an average of 41.2688 number of nodes (n), and migration/transmission time with an average of 4.203462 seconds (s).